Proceedings of the 2004 International Symposium on Underwater Technology (IEEE Cat. No.04EX869)
DOI: 10.1109/ut.2004.1405517
|View full text |Cite
|
Sign up to set email alerts
|

Development of a shallow water ambient noise database

Abstract: Abstract-The number of underwater activities and experiments in tropical waters has been growing; people are increasingly becoming interested in the development of underwater applications that rely on acoustic communications. Ambient noise is a limiting factor in the performance of underwater acoustic detection and communication systems at shallow water. Knowledge of ambient noise characteristics at a location will be helpful for ambient noise imaging systems like ROMANIS, built at Acoustic Research Laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The solutions to (2) are obtained using a NelderMeade optimisation routine [18]. This routine is started using 100 random initialisations; the random starting conditions are generated using uniform random numbers generated over the region [5,5] independently for each of the 3 coordinates. The final solution is obtained by selecting the solution which has the smallest cost function value from the 100 realisations.…”
Section: Source Localisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions to (2) are obtained using a NelderMeade optimisation routine [18]. This routine is started using 100 random initialisations; the random starting conditions are generated using uniform random numbers generated over the region [5,5] independently for each of the 3 coordinates. The final solution is obtained by selecting the solution which has the smallest cost function value from the 100 realisations.…”
Section: Source Localisationmentioning
confidence: 99%
“…[3] reported that specimens of snapping shrimp collected in the Bahamas kept in glass aquaria survived well as long as the water temperature remained between 14 o C and 24 o C. However, they also reported that the 11 o C winter seasurface isothermal line seemed to mark the approximate northern and southern limits of the range in which snapping shrimp live. Johnson et al [4] point out that the 11 o C isothermal line of the time passed some 7 o latitude (almost 800 km) South of southernmost England [5]. However there is some historical evidence of snapping shrimp in UK waters.…”
Section: Introductionmentioning
confidence: 99%
“…The paper also reviews the major problems in noise measurement, noise reduction, and its prevention. Pieng et al [8] highlight the collection of ambient noise data and the structured compilation of the collected information into a useful database. Kamal et al [9] present an attempt to lift the latent underwater source signals from the observed noise mixture utilizing independent component analysis (ICA).…”
Section: Related Workmentioning
confidence: 99%